EFFECTIVENESS AND EFFICIENCY ANALYSIS OF NIGHT AUDITOR FUNCTION TOWARD INTERNAL CONTROL AT HOTEL WO SURABAYA - Ryan Tivan Geri; Josephine Kurniawati Tjahjono; R. Bernardinus Chrisdianto (JOURNAL OF ACCOUNTING, ENTREPRENEURSHIP AND FINANCIAL TECHNOLOGY (JAEF), 2020)
The rapid development of hotels in Indonesia is making existing hotels have the urge to develop themselves to survive and compete. The bigger the hotel is, the more complex its activities will be. Internal control in the hotel is especially important so that no theft or neglection occurs from the internal side of the organization. In result, the hotel can operate optimally. The purpose of this study is to determine the effectiveness and efficiency of the night auditor function towards the internal control at Hotel WO, Surabaya. This research is based on a qualitative method. The object of this research is a private hotel in Surabaya and it has a three-star hotel rating. The subjects in this study includes officials and staffs who are directly experience the effectiveness and efficiency of the night auditor at Hotel WO in Surabaya. The data obtained in this study came from interviews and observations conducted at the hotel.The results of this study indicate that the night auditor at Hotel WO Surabaya has fulfilled several indicators of effectiveness, but not all. While the efficiency of the night auditor only meets one of the several indicators that have been determined in this study. The internal control at Hotel WO Surabaya is sufficient because double checks or re- examination of reports are always made. All reports made by the night auditor will be re- examined by the income auditor. Keywords: Night Auditor, Effectiveness, Efficiency.